FORGING SISTERHOOD WITHIN AND WITHOUT THE UNION: the Organizing Experience of MAKALAYA - Barrameda, Teresita Villamor (Philippine Journal of Social Development; 2008, 2010)
This article discusses the experience of the Manggagawang Kababaihang Mithi ang Paglaya or MAKALAYA in organizing women workers amid the worsening crisis brought about by globalization.  Against the backdrop of a globalized labor market, the feminization of labor in manufacturing and informal work and the shrinking of trade unions, MAKALAYA came into being to respond to the needs of women workers often ignored by trade unions.  In organizing women workers, MAKALAYA attempts to meld feminist perspective with “social movement unionism.” Veering away from the traditional trade union approach and adopting the “social movement unionism” concept, it combines trade unionism and community organizing to organize women in both formal and informal work.